(untitled) (Revista Psicología y Sociedad, 2025)
The approval of Law 2460 of 16 June 2025 by the Colombian Congress, which amends Law 1616 of 2013, represents an important change in mental health policy in this country. This article examines the new regulatory framework from a critical, analytical, and interpretative perspective where the central thesis of this law promotes a transition towards a more humane, comprehensive, and community-based care, aligned with international recommendations. However, this transformation faces structural and epistemological problems that hinder its implementation. The methodology of this paper is based on recent national and international sources, together with a critical analysis of the proposed legislative changes, and based on a critical review of recent academic and regulatory literature (2013-2025), selected based on criteria of timeliness, disciplinary relevance, and contribution to the understanding of public policies in mental health. The comparative analysis between laws was carried out under a socio-political interpretative approach. The results highlight the urgency of modifying professional training, consolidating territorial processes, and promoting greater collaboration between sectors and communities. In conclusion, the correct application of the Law will depend on the commitment of institutional actors, political will, and the collective construction of a new ethic of mental health care. This reflection raises future lines of action from psychology and the social sciences to support the normative transition towards a fairer, more participatory, and sustainable model.